Radarfacies and sedimentological analysis: study of sedimentary substrate from an archaeological site (shell mound), southern Brazil - Rodrigues, Selma Isabel; Porsani, Jorge Luis; Fonseca Giannini, Paulo Cesar; Fornari, Milene [UNESP]; Atorre, Tiago [UNESP]; DeBlasis, Paulo; Gaeta Ruiz, Daniella Magalhaes (Sage Publications Ltd, 2015)
Integrated results of GPR (Ground Penetrating Radar) and sedimentological analysis are presented for the Jabuticabeira II archaeological site (shell mound), Santa Catarina, Brazil. By means of radarfacies identification, this study aims to delimit the archaeological site and differentiate the coastal depositional systems that compose its substrates. For these purposes, available models of the temporal-spatial distribution of depositional systems in the area were used and sedimentological analysis (granulometry, quantification of heavy minerals and clay-mineral characterization) were performed on samples spaced at 0.5-m vertical intervals in auger drills cutting the identified radarfacies. GPR data were obtained along a radial grid, which allowed the rapid mapping of a large area (several hundred square metres). The results allowed to characterize an archaeological layer, the soil and two sedimentary layers (palaeolagoon and aeolian) in the substrates under and around the site. The high porosity and the grain size, cementation and heavy mineral segregation contrasts along wind-controlled laminations are for the reflector sharpness in the aeolian deposits. The archaeological site settlement mostly overlies the palaeolagoon, which was a newly emerged land during the epoch of occupation and is situated on the margins of aeolian deposits that formed in the region after the Holocene maximum flooding. This configuration reinforces the sambaquis occupation model of south-central Santa Catarina during the Holocene, strongly controlled by the proximity to lagoon bodies. The resolution of the data in this study was sufficient to advance our understanding of the regional sedimentary evolution and its relation with sambaqui occupation.
Keywords: Clay minerals; Grain-size distribution; Ground penetrating radar; Heavy minerals; Mineralogical fractionation; Shell mounds